MILITARY SYMBOLS OF THE ARMED FORMATIONS OF THE CARPATHIAN SICH AND THE UPA - Золкін, Дмитро; Сапицька, Олена (SWorldJournal, 2024)
The article examines the military symbols of the combat units of the Carpathian Sich and the Ukrainian Insurgent Army. It is noted that, having absorbed in its development the traditions of the UGA and USS, the military formations of the UNR, the military